USP2 Inhibits Lung Cancer Pathogenesis by Reducing ARID2 Protein Degradation via Ubiquitination. (15th December 2022) - Zhu, Lihuan; Chen, Zhizhong; Guo, Tianxing; Chen, Wenshu; Zhao, Lilan; Guo, Lingwen; Pan, Xiaojie
Abstract : Background . Ubiquitination is an important regulator in physiological and pathological conditions. Ubiquitin-specific protease 2 (USP2), as a member of the USP family, exhibits oncogenic effects in multiple malignancies. However, the exact role of USP2 has not been well clarified in lung cancer pathogenesis and progression. Therefore, we aimed to further investigate the regulatory roles of USP2 in lung cancer in this study. Methods . Firstly, immunoprecipitation-Mass Spectrometry (IP-MS), Co-immunoprecipitation (Co-IP), combined with immunofluorescent colocalization method, was conducted for USP2 protein interaction analysis in lung cancer cell lines. qRT-PCR, Western blot, and immunohistochemistry assays explored the USP2 expression pattern and USP2/ARID2- (AT-rich interactive domain 2-) specific shRNAs and overexpression vectors. Co-IP assays were designed to validate USP2-ARID2 protein interaction. Further functional studies including CHX chase assay, transwell assay, and wound healing assay were subsequently applied to evaluate the impact of USP2 modulation on lung cancer cells. Results . USP2 suppression was characteristic in lung cancer cell line models and lung cancer samples. USP2 and ARID2 demonstrated protein-protein interaction and overlapping localization in cancer cell models. Functional experiments suggested USP2 inhibited lung cancer cell invasion and migration by reducing ARID2 protein degradation. Subsequent ubiquitination assays indicated ARID2 protein degradation via the ubiquitination was significantly reduced by USP2 interaction. Conclusions . Our study provided novel insight that USP2 might suppress lung cancer by reducing ARID2 protein degradation via ubiquitination.